Vrednotenje kakovosti notranjega okolja visokošolske knjižnice - primer knjižnice Fakultete za gradbeništvo in geodezijo Univerze v Ljubljani - Koler-Povh, Teja (Knjižnica, 2019)
Purpose: The purpose of this article is to study the existing provisions for libraries in terms of librarianship and labour legislation to ensure comfort and safety in libraries, with an emphasis on higher education libraries. On the basis of the study results, the space of a sample higher education library of the Faculty of Civil and Geodetic Engineering at the University of Ljubljana will be evaluated. Methodology/approach: An overview of library and labour law provisions for higher education libraries has been carried out, and a model scheme of active zones of a sample higher education library of the Faculty of Civil and Geodetic Engineering at the University of Ljubljana (hereinafter UL FGG) has been formulated. The provisions and technical standards have been applied to the UL FGG sample library. A quality study of the sample library indoor environment was carried out, which included measurements of five parameters and evaluation. Results: Taking into account the recommendations of the IFLA principles and technical specifications for the safe and comfortable indoor library environment, the functional scheme for the UL FGG sample library was created. Based on the results of the performed measurements for selected parameters, we assessed the indoor environmental quality of the UL FGG library according to the provisions of library and work protection legislation. Research limitation: The study of the indoor environmental quality in the sample higher education library was carried out during the Spring Examination period, when the library operated in special conditions. Therefore, it would be useful to repeat it in the future and to re-evaluate the measurement results. Originality/practical implications: On the basis of legal and technical provisions, a functional scheme for the allocation of premises and equipment for the UL FGG sample library has been developed, which is also applicable to other higher education libraries. The methodology used for assessing the indoor environmental quality is in accordance with the IFLA principles. The recommended values of the selected parameters are precisely defined in the technical specifications and listed in the research results. They have a practical value for the construction or renovation of library buildings in the spirit of designing a safe and comfortable indoor environment for library visitors and staff as well as ensuring the conditions for quality storage of materials.
Keywords: kakovost; Ljubljana; notranje okolje; študija primera; tehnična določila; visokošolske knjižnice; zakonodaja